197 Alpha-5 Beta-1 Integrin: a Promising Therapeutic Target in the Field of Insulin Resistance and Cardiovascular Disease. (31st May 2014) - Haywood, Natalie; Yuldasheva, Nadira; Aziz, Amir; Smith, Jessica; Cordell, Paul; Kearney, Mark; Wheatcroft, Stephen
Abstract : Obesity is a key factor in the development of insulin resistance. Resistance to the vascular effects of insulin plays a central role in the initiation and progression of cardiovascular disease. Developing novel therapeutic strategies to prevent and treat insulin resistance is therefore important. IGFBP1 (Insulin like growth factor binding protein 1) is a 30kDa protein, derived mainly from the liver. We have previously shown that in vivo over expression of IGFBP1 improves insulin sensitivity, promotes nitric oxide production, lowers blood pressure and protects against atherosclerosis. IGFBP1 can impact on cellular functions via an RGD (α5 β1 integrin binding) motif independent of IGF binding. However, whether the integrin binding motif of IGFBP1 could be exploited therapeutically remained unexplored. The cell line C2C12, an insulin responsive skeletal muscle cell line, was used to investigate the effects with acute treatment of GRGDTP synthetic hexapeptide (which binds α5 β1 integrin) on the insulin signalling pathway, through immunoblotting of key insulin signalling proteins – IR (Insulin receptor), IRS1 (Insulin receptor substrate 1) and AKT (Protein kinase B). To investigate the possible role of integrin activation, the effects of acute treatment of GRGDTP on FAK (Focal adhesion kinase) phosphorylation were also investigated. C2C12 cells were also used in a glucose uptake assay, to determine the effects of GRGDTP on insulin stimulated glucose uptake. To examine whether the RGD motif of IGFBP1 could be exploited therapeutically synthetic hexapeptide GRGDTP was administered to C57BL/6 mice with diet-induced obesity. Treatment with GRGDTP prior to insulin stimulation of C2C12 cells enhances FAK, IRS1 and AKT phosphorylation (P ≤ 0.05). Treatment with GRGDTP prior to insulin stimulation of C2C12 cells increased insulin stimulated glucose uptake (P ≤ 0.01). Acute administration of GRGDTP (40 μg IP) significantly improved glucose tolerance (P ≤ 0.05) and insulin sensitivity in C57BL/6 mice with diet-induced obesity (P ≤ 0.05). For the first time, we have shown that the integrin binding domain of IGFBP1 may play an important role in insulin sensitivity and glucose regulation and represents a promising therapeutic agent in the field of insulin resistance and cardiovascular disease.